2014
DOI: 10.1016/j.foodchem.2014.05.083
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of polyphenols from water chestnut (Trapa japonica) husk on glycolytic enzymes and postprandial blood glucose elevation in mice

Abstract: Water chestnut is an annual aquatic plant that grows in Asia and Europe. Although water chestnut has been used as food and herbal medicine, its physiological functions and active ingredients are unknown. Here, we extracted polyphenols from the husk of the Japanese water chestnut (Trapa japonica) and assessed their effects on blood glucose levels. Three hydrolysable polyphenolics (WCPs), eugeniin, 1,2,3,6-tetra-O-galloyl-β-d-glucopyranose, and trapain, were predominant with dry-weight contents of 2.3 ± 0.0, 2.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…So, the extractions with methanol resulted in the highest amount of the total extractable compounds than in the remaining solvents, which is in agreement with the report of Ao, Li, Elzaawely, Xuan, & Tawata (2008). Midori et al (2014) also confirmed the presence of polyphenols in water-chestnut husk.…”
Section: Assay For Antioxidant Activity Total Phenolssupporting
confidence: 90%
See 1 more Smart Citation
“…So, the extractions with methanol resulted in the highest amount of the total extractable compounds than in the remaining solvents, which is in agreement with the report of Ao, Li, Elzaawely, Xuan, & Tawata (2008). Midori et al (2014) also confirmed the presence of polyphenols in water-chestnut husk.…”
Section: Assay For Antioxidant Activity Total Phenolssupporting
confidence: 90%
“…The sample solution showed antiproliferative activity against Colo-205, T47D, and MCF7 and it significantly reduced the growth rate of cancer cells at a concentration of 50 µg/mL after 24 h treatment, however, the maximum effect was on Colo-205, as shown in Figure 5. The presence of various bioactive compounds like glycosides, flavonoids, phytosterols, and tannins (Shalabh et al, 2012) in the extract of T. natans and the polyphenols like trapain, euginin, and 1,2,3,6-tetra-O-galloyl-beta-D-glucopyranose (TGG) reported by Midori et al (2014) in the husk of T. natans may be responsible for anticancerous activities (Li et al, 2013;Ravishankar, Rajora, Greco, & Osborn, 2013). Yuan and Walsh (2006) reported dose-dependent inhibition against the proliferation of the human cervical epithelial adenocarcinoma HeLa cell line in the case of dulse and kelp extracts, which also have aquatic habitats as water chestnut.…”
Section: Antiproliferative Assaymentioning
confidence: 99%
“…Water chestnut extracts are also reported to have high inhibitory activity against glycolytic enzymes such as aamylase that inhibits blood glucose elevation and a unique feature of reducing insulin secretion and hence can be effective food additives in managing type 2-diabetes (Yasuda et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The fruit contains approximately 80% starch, 5% protein, and a significant amount of vitamins [19]. The recent investigation revealed polyphenols, eugeniin, 1,2,3,6-tetra-O-galloyl-β-d-glucopyranose, and trapain from the husk of the TJF [20]. Most studies evaluating TJF have focused on its taxonomy and ecology [18] [21].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies evaluating TJF have focused on its taxonomy and ecology [18] [21]. TJF has been known to have anti-oxidative, anti-cancer and anti-diabetic effects, reduction of blood glucose levels, and inhibitory activity against α-amylase and α-glucosidase [20] [22]- [24]; however, the effects of TJF on anti-adipogenesis have not been investigated yet. In the present study, we examined whether TJF extract affects adipocyte differentiation, and the expression of adipogenic transcription factors and related proteins in 3T3-L1 cells.…”
Section: Introductionmentioning
confidence: 99%